Manajemen Pendidikan Untuk Daerah Terpencil: Perbandingan Strategi Pemerataan Akses di Indonesia dan Malaysia - Multi; Wany Nurhani; Sri Narti Rabrusun; Edi Ahyani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Ambon, 2025)
Education is a fundamental right for every individual, including those living in remote areas. However, limitations in access and infrastructure often pose a major barrier to achieving educational equity. This study aims to evaluate methods for mapping educational access in remote areas in Indonesia and Malaysia. The methodology used is a descriptive qualitative study with a comparative approach, analyzing government policies, strategic programs, and implementation outcomes in both countries. The research findings indicate that Indonesia and Malaysia implement different approaches to mapping and reaching remote areas. Indonesia prioritizes strengthening spatial databases and intersectoral collaboration, while Malaysia prioritizes the application of digital technology and community-based infrastructure development. Both approaches have their own advantages and challenges. The results of this study are expected to serve as considerations and references for policymakers in formulating more inclusive and equitable education policies across all regions, especially for less developed and difficult-to-reach areas. Keywords: Education for remote areas, comparison of strategies, equitable access in Indonesia and Malaysia